2021
DOI: 10.1007/s42448-020-00065-3
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Safety and Child Protection Responses in Hospitals: a Scoping Review

Abstract: The objective of this scoping review was to map the current practice and best evidence for embedding cultural safety in child protection responses for Aboriginal families in hospitals. Electronic databases were searched systematically and the reference lists examined. Efforts to reduce the risk of bias were made including using an inductive approach. Eight research papers were included following the exclusion of 25 papers for the final analysis. Three main themes in relation to what is necessary to embed cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The aim of cultural safety is to promote a more equal society and provide care that is experienced as "safe" by the individuals and communities receiving care (Congress of Aboriginal & Torres Strait Islander Nurses & Midwives, 2014; Curtis et al, 2019). Enacting culturally safe approaches involves genuine partnership and engagement with First Nations people, but there is limited research into ways that culturally safe approaches can be implemented and enacted in health services (Flemington et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of cultural safety is to promote a more equal society and provide care that is experienced as "safe" by the individuals and communities receiving care (Congress of Aboriginal & Torres Strait Islander Nurses & Midwives, 2014; Curtis et al, 2019). Enacting culturally safe approaches involves genuine partnership and engagement with First Nations people, but there is limited research into ways that culturally safe approaches can be implemented and enacted in health services (Flemington et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our scoping review [33] found three central intersectional themes to embedding cultural safety in health professional child protection responses for Aboriginal children in hospital settings. These themes were: relationships; organisational processes; and culture.…”
Section: Phase 3: Scoping Literature Reviewmentioning
confidence: 98%
“…It focusses on four domains-landscape factors, resources, ways of working and learnings. They in turn complement the i-PARIHS Framework domains of facilitation, innovation, recipients and context, as detailed elsewhere [33].…”
Section: Phase 1: Developing Appropriate Governance and Oversightmentioning
confidence: 99%
See 2 more Smart Citations